The impact of COPD and smoking history on the severity of COVID‐19: A systemic review and meta‐analysis - Zhao, Qianwen; Meng, Meng; Kumar, Rahul; Wu, Yinlian; Huang, Jiaofeng; Lian, Ningfang; Deng, Yunlei; Lin, Su (Journal of medical virology, 2020)
Comorbidities are associated with the severity of coronavirus disease 2019 (COVID‐19). This meta‐analysis aimed to explore the risk of severe COVID‐19 in patients with pre‐existing chronic obstructive pulmonary disease (COPD) and ongoing smoking history. A comprehensive systematic literature search was carried out to find studies published from December 2019 to 22 March 2020 from five databases. The languages of literature included English and Chinese. The point prevalence of severe COVID‐19 in patients with pre‐existing COPD and those with ongoing smoking was evaluated with this meta‐analysis. Overall 11 case series, published either in Chinese or English language with a total of 2002 cases, were included in this study. The pooled OR of COPD and the development of severe COVID‐19 was 4.38 (fixed‐effects model; 95% CI: 2.34‐8.20), while the OR of ongoing smoking was 1.98 (fixed‐effects model; 95% CI: 1.29‐3.05). There was no publication bias as examined by the funnel plot and Egger's test (P = not significant). The heterogeneity of included studies was moderate for both COPD and ongoing smoking history on the severity of COVID‐19. COPD and ongoing smoking history attribute to the worse progression and outcome of COVID‐19.